Foraging in the Anthropocene: exploring the dynamics of reservoir and plastic pollution in freshwater organisms. - Yofukuji, Kátia Yasuko (2024)
Freshwater ecosystems face serious threats in our increasingly human-dominated world, particularly from pressures such as impoundment and plastic pollution due to mismanagement of plastic waste. Both anthropic disturbances have been linked to global declines in freshwater area and biodiversity. Evaluating how these disturbances affect organisms is of extremely importance for conservation purposes and the implementation of effective public policies and management strategies.The effects of river impoundment and plastic pollution through the lens of fish trophic ecology were assessed. A global synthesis was conducted to unravel the current knowledge on plastic occurrence regarding freshwater fish and invertebrates. The trophic ecology of fish from the Itaipu reservoir was assessed, revealing shifts in diet and trophic structure along longitudinal gradients induced by damming. The transition from predominantly allochthonous to autochthonous resources significantly influenced the spatial distribution of trophic guilds across the reservoir. We highlighted changes in dominant guilds with the reservoir's aging, particularly the rise and fall of planktivores and aquatic insectivores. Microplastic occurrence in a Neotropical fish community was evaluated. Low incidence of plastic ingestion was evident, with fibers and fragments of plastics identified as polyamide, polystyrene, and polyethylene. Fish from the lacustrine zone, insectivores, and benthopelagic species showed a significant correlation with plastic ingestion. A systematic review synthesizing literature on plastic occurrence in freshwater fish and invertebrates was conducted globally. It was highlighted that reporting on plastic occurrence has primarily focused on fish, with recent efforts acknowledging the threat to invertebrates. Biological and ecological factors were explored to influence plastic prevalence, revealing limited predictive power for increased plastic occurrence in both groups, emphasizing the vulnerability of both taxa to plastic pollution. We emphasize the critical need to understand and address the impacts of impoundment and plastic pollution on freshwater ecosystems to ultimately safeguard freshwater biodiversity.